Dinâmica de marcadores salivares de atividade autônoma e adrenocortical em resposta à competição de elite - Gómez, Miguel Mauricio Díaz (2011)
CHAPTER 2: This study examined the variation in the cortisol awakening response (CAR) in relation to mood states and performance during professional swimming competition. Eleven athletes were examined during two consecutive days of competition. On each day salivary cortisol was determined upon awakening, 30 and 60 min post awakening, immediately before warming up for competition and 5, 20 and 60 min after competition. Psychometric instruments included the Profile of Mood States and self-reports of performance. CARs did not differ between competition and non-competition days and were not related to performance on any day. However, difference was observed in the concentration of cortisol prior to and after the contest between competition and non-competition days. Perceived demands of the day ahead might not reflect the same magnitude of variation in the CAR in well-trained men. Explanations for this include better coping mechanisms and response towards the phase and time of competition. CHAPTER 3: Objective: We investigated the response of salivary total protein (TP), alpha-amylase (sAA) and chromogranin A (CgA) to sporting competition and their relation with positive and negative affect. Methods: Eleven professional swimmers were examined during the first day of a national contest and on a recreated event that matched time-of-the-day and day-of-theweek assessments two weeks later. Total protein was determined by the Bradford method and sAA and CgA by western blotting upon awakening, 30 and 60 min post awakening, immediately before warming up for competition and 5, 20 and 60 min after competition. Psychometric instruments included the Positive Affect and Negative Affect Schedule - X (PANAS-X). Results: The concentrations of TP, sAA and CgA differed from controls only prior to and 5 min after the event. We observed associations between higher negative affect scores with higher levels of TP, sAA and CgA prior to the event on the competition day. Areas under the curve did not differ from controls for TP, sAA or CgA. Conclusion: TP and CgA showed a similar reactivity to sporting competition than sAA, which may be attributed to the mechanisms responsible for protein secretion into saliva when collection is performed with no exogenous stimulation. Strong adverse psychological stimuli only seem to override the regular rhythm of salivary proteins moments before and after stressful situations.